Anion exchange membrane test protocol validation - Ahn, Su Min; Boudreau, Andrew; Ekennia, Anthony C.; Palau, Alexis; Vulpin, Olivia T.; Kwak, Minkyoung; Kim, Yu Seung; Boettcher, Shannon W.; Park, Eun Joo; Roberts, George M.; Perez Bakovic, Sergio I.; Ayers, Katherine E. (Frontiers in Energy Research, 2025)
This study presents the validation of protocols for measuring ion exchange capacity (IEC) and alkaline stability of anion exchange membranes (AEMs) for low-temperature water electrolysis. While protocols are often tested within individual laboratories, their results across multiple laboratories with varying equipment, environmental conditions, and personnel qualification remain unverified. The validation involved Los Alamos National Laboratory (LANL), National Renewable Energy Laboratory (NREL), and University of Oregon (UO) using the same commercially available AEM to assess reproducibility and reliability of the protocols under diverse conditions. For the IEC protocol, results across laboratories were consistent within ±10% of the NMR-determined reference value. The alkaline stability protocol could pose greater challenges due to factors such as variations in sample collection timing, preservation methods, and analytical techniques, but consistent test results for percentage IEC loss were demonstrated across institutions. These results highlight the reliability and applicability of the protocols, emphasizing the importance of validation to ensure consistency in diverse research environments.